Adoption of GIS, GPS and RS Techniques in the Sudanese Sugarcane Industry: Part 1- Kenana Base Map Establishment (University of Khartoum Engineering Journal, 2022)
The objective of this study is to explore the adoption of Geographical Information System (GIS), Global Positioning System (GPS), Remote Sensing (RS), and related techniques in the Sudanese sugarcane industry for agricultural production management as a response to the feedback from the academia on sugar industry. Framework on the adoption of the initiative program included techniques capacity building, base map establishment, and crop monitoring and assessment. Extensive in-house training and attended seminars were carried out by the academia to targeted personnel to highlight the opportunities pertinent to the success planning, implementation and management of these techniques on sugarcane industry. High resolution Satellite image data and GIS technique were used to establish Kenana Sugar Company (KSC) base map. Various map layers such as field layout, irrigation network, soil type, roads network, civil work were prepared using remotely sensing data along with the existing maps. Twelve ground reference points were established. The field layout map layer is divided into six areas and each area is divided into two farms having three sections for each. The soil map layer is qualitatively classified into four soil categories based on the tonnage produced. The irrigation network map layer consisted of six pump stations, main canals, primary canals, field canals, regulators, and drainage network. The road network map layer showed the major and minor roads that had been used as a platform for Vehicle Tracing System (VTS) for hauling sugarcane, while the civil work layer located the factory, administrative and residential area. Based on the obtained results, this study provides sample evidence that sugar industry could use GIS, GPS, RS and related techniques to enhance the management of sugarcane production.